Hubungan antara Citra Merek dan Kualitas Produk terhadap Keputusan Membeli Laptop - Udhiyantik, Fitri Wahyu; Parlyna, Ryna; Hidayat, Nurdin (Jurnal Bisnis, Manajemen, dan Keuangan, 2020)
The purpose of this study is to determine the correlation between brand image and product quality with purchase decision laptop Asus in The Faculty of Economics Student in State University of Jakarta. This research was conducted in The Faculty of Economics Student in State University of Jakarta, for 6 months, starting from January to June 2019. The research method used is survey method with the correlation approach, population used are all student in The Faculty of Economics Student in State University of Jakarta. The sampling technique used technique of purposive sampling as many as 106 people. There data were collected with questionnaire and analyzed with SPSS version 22.0. The results of this study concluded that (1) the brand image has a positive and significant relationship with purchase decision, (2) the product quality has a positive and significant relationship with purchase decision, (3) the variable purchase decision is determined by the brand image and product quality.